Advertisements
Advertisements
Question
If `log (x^2 + y^2) = 2 tan^-1 (y/x)`, show that `(dy)/(dx) = (x + y)/(x - y)`
Solution
We have, `log (x^2 + y^2) = 2 tan^-1 (y/x)`
⇒ `(1)/(2) log (x^2 + y^2) = tan^-1 (y/x)`
Differentiate with respect to x, we get,
⇒ `(1)/(2) (d)/(dx) log (x^2 + y^2) = (d)/(dx) tan^-1 (y/x)`
⇒ `(1)/(2) ((1)/(x^2 + y^2)) (d)/(dx) (x^2 + y^2) = (1)/(1+ (y/x)^2) (d)/(dx) (y/x)`
⇒ `(1)/(2) ((1)/(x^2 + y^2)) [2x + 2y (dy)/(dx)] = (x^2)/((x^2 + y^2)) [(x (dy)/(dx) - y (d)/(dx) (x))/(x^2)]`
⇒ `((1)/(x^2 + y^2)) (x + y (dy)/(dx)) = (x^2)/((x^2 + y^2)) [(x (dy)/(dx) - y(1))/(x^2)]`
⇒ `((1)/(x^2 + y^2)) (x + y (dy)/(dx)) = (x^2)/((x^2 + y^2)) [(x (dy)/(dx) - y(1))/(x^2)]`
⇒ `x + y (dy)/(dx) = x (dy)/(dx) - y`
⇒ `y(dy)/(dx) - x(dy)/(dx) = -y - x`
⇒ `(dy)/(dx) (y - x) = - (y + x)`
⇒ `(dy)/(dx) = (-(y + x))/(y - x)`
⇒ `(dy)/(dx) = (x + y)/(x - y)`
RELATED QUESTIONS
Differentiate `cos^-1((3cosx-2sinx)/sqrt13)` w. r. t. x.
If `y=sin^-1(3x)+sec^-1(1/(3x)), ` find dy/dx
Find the derivative of the following function f(x) w.r.t. x, at x = 1 :
`f(x)=cos^-1[sin sqrt((1+x)/2)]+x^x`
if `y = sin^(-1)[(6x-4sqrt(1-4x^2))/5]` Find `dy/dx `.
If `y=tan^(−1) ((sqrt(1+x^2)+sqrt(1−x^2))/(sqrt(1+x^2)−sqrt(1−x^2)))` , x2≤1, then find dy/dx.
Find `dy/dx` in the following:
`y = tan^(-1) ((3x -x^3)/(1 - 3x^2)), - 1/sqrt3 < x < 1/sqrt3`
Find `dy/dx` in the following:
`y = sin^(-1)(2xsqrt(1-x^2)), -1/sqrt2 < x < 1/sqrt2`
Differentiate w.r.t. x the function:
`(sin x - cos x)^(sin x - cos x), pi/4 < x < (3pi)/4`
Find `dy/dx, if y = sin^-1 x + sin^-1 sqrt (1 - x^2) , 0<x <1`
If `xsqrt(1+y) + y sqrt(1+x) = 0`, for, −1 < x <1, prove that `dy/dx = 1/(1+ x)^2`
If `sqrt(1-x^2) + sqrt(1- y^2)` = a(x − y), show that dy/dx = `sqrt((1-y^2)/(1-x^2))`
Differentiate `tan^(-1) ((1+cosx)/(sin x))` with respect to x
Solve `cos^(-1)(sin cos^(-1)x) = pi/2`
Find \[\frac{dy}{dx}\] at \[t = \frac{2\pi}{3}\] when x = 10 (t – sin t) and y = 12 (1 – cos t).
If y = (sec-1 x )2 , x > 0, show that
`x^2 (x^2 - 1) (d^2 y)/(dx^2) + (2x^3 - x ) dy/dx -2 = 0`
If y = cos (sin x), show that: `("d"^2"y")/("dx"^2) + "tan x" "dy"/"dx" + "y" "cos"^2"x" = 0`
If y = sin-1 x + cos-1x find `(dy)/(dx)`.
If `"y" = (sin^-1 "x")^2, "prove that" (1 - "x"^2) (d^2"y")/(d"x"^2) - "x" (d"y")/(d"x") - 2 = 0`.
If y = `(sin^-1 x)^2,` prove that `(1-x^2) (d^2y)/dx^2 - x dy/dx -2 = 0.`
Trigonometric and inverse-trigonometric functions are differentiable in their respective domain.
`lim_("h" -> 0) (1/("h"^2 sqrt(8 + "h")) - 1/(2"h"))` is equal to ____________.
`lim_("x"-> 0) ("cosec x - cot x")/"x"` is equal to ____________.
`"d"/"dx" {"cosec"^-1 ((1 + "x"^2)/(2"x"))}` is equal to ____________.
If y `= "cos"^2 ((3"x")/2) - "sin"^2 ((3"x")/2), "then" ("d"^2"y")/("dx"^2)` is ____________.
The derivative of `sin^-1 ((2x)/(1 + x^2))` with respect to `cos^-1 [(1 - x^2)/(1 + x^2)]` is equal to
If y = sin–1x, then (1 – x2)y2 is equal to ______.
Differentiate `sec^-1 (1/sqrt(1 - x^2))` w.r.t. `sin^-1 (2xsqrt(1 - x^2))`.